Modelling seasonal fluctuations and aspect characteristics of ice-cliff melt on the debris-covered Trakarding Glacier, Rolwaling Valley, Nepal Himalaya - Yota Sato; Pascal Buri; Marin Kneib; Evan S. Miles; Sojiro Sunako; Tika R. Gurung; Akiko Sakai; Francesca Pellicciotti; Koji Fujita (Journal of Glaciology)
Ice cliffs on debris-covered glaciers act as melt hotspots that considerably enhance glacier ablation. However, studies are typically limited in time and space; glacier-scale studies of this process of ice cliff melt are rare, and their varying seasonal energy balance remains largely unknown. In this study, we combined a process-based ice cliff backwasting model with high-resolution (1.0 m) photogrammetry-based terrain data to simulate the year-round melt of 479 ice cliffs on Trakarding Glacier, Nepal Himalaya. Ice cliff melt accounted for 26% of the mass loss of the glacier from October 2018 to October 2019, despite covering only 1.7% of the glacier surface. The annual melt rate of ice cliffs was 2.7 cm w.e. d−1, which is 8–9 times higher than the sub-debris melt rate. Ice cliff melt rates were significantly controlled by their aspects, with south-facing ice cliffs showing a melt rate 1.8 times higher than that of north facing ones. The results revealed that the aspect dependence of ice cliff melt rate was amplified in winter and decreased/disappeared toward the monsoon season. The seasonal changes in melt characteristics are considered to be related to variations in direct shortwave radiation onto the cliff surface, which are dependent on changes in solar altitude and monsoonal cloud cover.